Страхование: учебник - Базанов А. Н. Андрей Николаевич; Белинская Л. В. Лариса Викторовна; Власов П. А. Павел Алексеевич; Голубятников А. А.; Чернова Г. В. (Москва, Проспект, 2007)
Исключено из фонда НТБ ТПУ